Food Support For The Andalas University Students During The First Lockdown Due To The Covid-19 Pandemic - Wellyalina, Wellyalina; Hasbullah, Hasbullah; Cesar Welya, Refdi; Azrifirwan, Azrifirwan; Feri, Arlius (Andalasian International Journal of Social and Entrepreneurial Development, 2021)
Background: Distributing Food Supplies for andalas university students that wander in Padang whoare affected by the Covid-19 Pandemic is essential. Methodology: The distribution of basic food packagesconsisting of rice, eggs, cooking oil, milk and instant noodles has been carried out in 2 stages. This packagecan feed students for 1 week and help them to survive this difficult time. This program was directlysupervised by the Dean of the Faculty of Agricultural Technology, Andalas University and implementedjointly with all members of the Faculty of Agricultural Technology, Andalas University. Conclusion: Thisactivity can increase solidarity with the care of others affected by Covid-19 and also encourageunderstanding and interest in community empowerment, especially in tackling the spread of coronavirus